ANALISIS PERMINTAAN DEPOSITO BERJANGKA RUPIAH PADA BANK UMUM DI SUMATERA UTARA TAHUN 2001-2010 - Arno Richarto Gultom; Raina Linda Sari (Departemen Ekonomi Pembangunan USU, 2014)
The main purpose of this research was to analyze the factors that affect demand deposits at commercial banks in North Sumatera. The variables that affect demand in the considered time deposits and the research object are PDRB, the interest rate on time deposits and inflation rat. This research also aims to investigate the contribution of each variable on the demand for time deposits at commercial banks in North Sumatera. To achieve the purpose of analysis, this study used time series data with a range of time during the years 2001 -2010 in quarter to quarter. The method used to estimate this research is to analyze Ordinary Least Square (OLS) in estimating the results of research. The results found that the variable deposit rate, gross domestic product, and demand deposits of one year before a positive and significant impact on demand for time deposits at commercial banks in North Sumatera.Keywords : Demand Deposit , PDRB, the interest rate , inflation rate